2012
DOI: 10.1088/0957-4484/23/30/305708
|View full text |Cite
|
Sign up to set email alerts
|

InGaN quantum dot formation mechanism on hexagonal GaN/InGaN/GaN pyramids

Abstract: Growing InGaN quantum dots (QDs) at the apex of hexagonal GaN pyramids is an elegant approach to achieve a deterministic positioning of QDs. Despite similar synthesis procedures by metal organic chemical vapor deposition, the optical properties of the QDs reported in the literature vary drastically. The QDs tend to exhibit either narrow or broad emission lines in the micro-photoluminescence spectra. By coupled microstructural and optical investigations, the QDs giving rise to narrow emission lines were conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…11, 26 The full-width half-maxima of the emission peaks in the present case are relatively broad (. 4 meV).…”
Section: Multiple Ingan Qds On a Gan Ehpmentioning
confidence: 60%
“…11, 26 The full-width half-maxima of the emission peaks in the present case are relatively broad (. 4 meV).…”
Section: Multiple Ingan Qds On a Gan Ehpmentioning
confidence: 60%
“…12 A promising approach for fabrication of nitride-based QDs is to deposit a thin layer of InGaN on top of hexagonal GaN micro pyramids formed by selective area growth. 13 Pyramids grown with this approach have been shown to exhibit single and sharp InGaN related emission lines with high degree of linear polarization, indicating the formation of one asymmetric site-controlled InGaN quantum dot on each pyramid. 14 Moreover, a simple elongation of the pyramid base gives control of the polarization direction of the InGaN emission, as it is found to be well-aligned with the designed elongation.…”
mentioning
confidence: 94%
“…The structure is then covered by a layer of GaN to finalize the formation of QD inclusions in the tip of the pyramids. 13 The pyramids have a base diameter of 3 lm, and they are ordered in square 21 Â 21 arrays with 5.5 lm pitch.…”
mentioning
confidence: 99%
“…The potential of such pyramids for the growth of arrays of InGaN nanostructures was identified long ago: indeed, deposition of InGaN on fully formed, untruncated GaN pyramids and further covering with GaN barrier/cap layer leads to the formation of inclined InGaN quantum wells on the side facets [26]. In addition, it has been further demonstrated that this technique also leads to formation of QDs at the apex of the pyramid [27,28].…”
Section: Selective Area Growth Of Nwsmentioning
confidence: 99%